Study on distribution characteristics of wind speed field in the sea area of Ly Son island of Quang Ngai province - Chung, Tran Van; Tien, Ngo Manh; Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2021)
On the basis of the data source of the 10 m wind field above the sea with the hourly frequency and during the period of 41 years (1979–2019) by the NCEP CFRS, we used the probability distribution functions to study the distribution law of wind speed in the waters of Ly Son island. Specifically, four distribution functions (normal distribution, gamma distribution, Weibull distribution and extreme value distribution) were used to estimate the characteristic parameters of the shape and proportion of the wind distribution in the waters of Ly Son island.